The development of embedded negative input shaping for vibration control of a flexible manipulator by using PIC controller - Liew, Yoong Sang (2009)
Negative input shaping is one of the techniques used to reduce residual vibration in the flexible manipulator system. An unshaped bang-bang torque input is used to determine the characteristic parameters of the system. The results of response of the manipulator to the shaped inputs are presented in time and frequency domains. But there is a challenging problem exists in the manipulator system because it is difficult to maintain the accurate positioning. To overcome this problem, feedforward control will consider as the vibration control schemes. Feed-forward involved the control inputs depend on the physical and vibration properties of the system. This technique is more advantage since there are no additional sensors and actuators needed. Results from negative input shaping will show the response of manipulator system has reduced in level of vibration. It is proved that when increase the number of impulses of the specified negative amplitude (SNA) shapers, the level of vibration reduction also increase. There are three specified negative amplitude shapers used in the system. From first order impulse, it has SNA Zero Vibration (ZV), Zero Vibration Derivative (ZVD) and Zero Vibration Derivative Derivative (ZVDD).